2020
DOI: 10.1101/2020.06.26.174698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A facile Q-RT-PCR assay for monitoring SARS-CoV-2 growth in cell culture

Abstract: 19Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of the 20 ongoing COVID-19 pandemic, has infected millions within just a few months and is continuing to 21 spread around the globe causing immense respiratory disease and mortality. Assays to monitor 22 SARS-CoV-2 growth depend on time-consuming and costly RNA extraction steps, hampering 23 progress in basic research and drug development efforts. Here we developed a facile Q-RT- 24PCR assay that bypasses viral RNA extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…While these open-source approaches may not match the exquisite sensitivity of expensive commercial kits, testing centers must consider whether some reduction in sensitivity is worth increased availability of tests in the face of economic and logistical constraints. Continued refinement of open-source diagnostic methods and their adoption by "pop-up" testing centers [26,46,47] could facilitate expanded testing, both in the current pandemic and in response to novel viruses in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these open-source approaches may not match the exquisite sensitivity of expensive commercial kits, testing centers must consider whether some reduction in sensitivity is worth increased availability of tests in the face of economic and logistical constraints. Continued refinement of open-source diagnostic methods and their adoption by "pop-up" testing centers [26,46,47] could facilitate expanded testing, both in the current pandemic and in response to novel viruses in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Validating BEARmix for clinical diagnostics would of course require more extensive side-by-side comparison of BEARmix and a commercial master mix in an actual testing center, and it is likely that the relative performance of BEARmix and other master mixes may differ depending on the primer set used [13]. Additionally, it would be interesting to evaluate BEARmix in combination with direct-addition protocols for saliva testing [46,47]. This basic master mix recipe could be improved in various ways, for instance, by including dUTP and UDG to prevent amplicon contamination, optimizing the conditions for hot-start Taq preparation and reactivation, or testing other public-domain DNA polymerase and reverse transcriptase variants [48].…”
Section: Plos Onementioning
confidence: 99%
“…Extracted RNA was either subjected to Q-RT-PCR analysis for viral RNAs, cellular RNA, or RNA-seq. Viral RNA in cell culture supernatants was quantitated as detailed before (Shema Mugisha et al, 2020b). In brief, 5 μL of supernatant was mixed with 5 μL of 2x lysis buffer (2% Triton X-100, 50mM KCl, 100mM TrisHCl pH7.4, 40% glycerol supplemented with 400u/mL of SuperaseIN (Life Technologies)), followed by addition of 90 μL of 1X core buffer (5 mM (NH4)2SO4, 20 mM KCl and 20 mM Tris–HCl pH 8.3).…”
Section: Star Methodsmentioning
confidence: 99%
“…10 μL of this sample was used in a TaqMan-based Q-RT-PCR assay using TaqMan™ RNA-to-CT™ 1-Step Kit (Applied Biosystems, #4392938), alongside with RNA standards, targeting SARS-CoV-2 N gene. The primers and probe sequences are as described before (Shema Mugisha et al, 2020b). To study the interferon (IFN) response, cellular RNA was reverse transcribed with High-Capacity cDNA Reverse Transcription kit (Thermo Fisher Scientific) followed by Q-RT-PCR analysis using PowerUp SYBR Green Master Mix (Applied Biosystems).…”
Section: Star Methodsmentioning
confidence: 99%
“…Generally, HIV protease inhibitors are used in combination with at least two other anti-HIV drugs (Sadler et al, 2020). Recent in vitro studies demonstrated that amprenavir exhibited a considerable degree of inhibition against SARS-CoV-2 (Mugisha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%